A broad bean extract corrosion inhibitor, preparation method and application

By using bioactive substances in broad bean extract to form a protective film, the problems of self-corrosion of zinc anode and dendrites of zinc air battery are solved, the Coulomb efficiency and service life of the battery are improved, and safety hazards are reduced.

CN119776842APending Publication Date: 2025-04-08JIXIAN GREEN FUNCTIONAL MATERIALS RESEARCH CENTER
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411909116.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

In alkaline solution, zinc anode is prone to self-corrosion and dendrite growth, resulting in reduced reversibility and Coulomb efficiency, affecting the normal operation and safety of the battery.

Method used

Broad bean extract is used as a corrosion inhibitor to form a protective film through biologically active substances such as polyphenol compounds and flavonoid compounds to inhibit the electrochemical corrosion reaction of the zinc anode.

Benefits of technology

It significantly improves the Coulomb efficiency and anode utilization rate of zinc air batteries, extends the service life of the battery, and reduces safety hazards.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119776842A_ABST
    Figure CN119776842A_ABST
Patent Text Reader

Abstract

The invention provides a broad bean extract corrosion inhibitor, a preparation method and an application thereof, and relates to the technical field of zinc-air batteries. The invention comprises the following steps: S1: washing broad beans with deionized water, and grinding the broad beans into broad bean powder by a grinder after drying; S2: adding the broad bean powder to deionized water and boiling for 3-5 hours, removing filter residue by vacuum filtration, and obtaining a filtrate containing broad bean extract and water; S3: putting the filtrate into a culture dish, sealing the open opening of the culture dish with a plastic wrap, and putting the dish into a refrigerator for freezing; S4: rolling holes in the frozen sample for vacuum freeze drying, and finally obtaining the broad bean extract, i.e., the corrosion inhibitor; in the invention, the broad bean extract is used as the corrosion inhibitor, so that the electrochemical stability window of the electrolyte is broadened and the stability of the electrolyte is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of zinc-air batteries, and in particular to a broad bean extract corrosion inhibitor, a preparation method and an application thereof. Background Art

[0002] In today's material field, zinc metal has attracted much attention due to its unique characteristics. Zinc has good corrosion resistance and can form a dense oxide film in the atmospheric environment, which effectively protects its internal structure and prolongs its service life. In addition, zinc resources are relatively abundant, the cost is relatively low, and it is easy to obtain and process. However, zinc metal still faces corrosion problems in acidic or alkaline solutions. This corrosion phenomenon will not only greatly reduce the service life of zinc materials, but also is very likely to cause environmental pollution problems, and there are also certain safety hazards.

[0003] Zinc-air batteries are an ideal energy source for electric vehicles. The working principle is to use oxygen as the positive active substance and metal zinc as the negative electrode to generate electricity by electrochemical reaction between zinc and oxygen. Because it is carried out under alkaline solution conditions, the zinc surface will self-corrode and grow dendrites, resulting in reduced reversibility and coulomb efficiency, and even affecting the normal operation of the battery, posing a great safety hazard. Therefore, the protection of the zinc anode in the zinc-air battery is very necessary.

[0004] In order to respond to the policy of green emission reduction, energy conservation and environmental protection, a broad bean extract corrosion inhibitor, a preparation method and an application are urgently needed. Summary of the invention

[0005] Based on this, the present invention provides a broad bean extract corrosion inhibitor, a preparation method and an application thereof, which solve the problems of high toxicity, environmental pollution, high cost and complex synthesis of existing corrosion inhibitors, and also solves the technical problems of low anode utilization and fast corrosion rate caused by hydrogen evolution corrosion, irregular dendrite growth and reduced Coulomb efficiency of zinc-air batteries under the existing technical conditions. In order to solve the above technical problems, one of the objects of the present invention is to provide a method for preparing a broad bean extract corrosion inhibitor, such as Figure 1 As shown, the following steps are included: S1: Wash broad beans with deionized water, dry them, and grind them into broad bean powder using a grinder; S2: adding broad bean powder to deionized water and boiling for 3-5 hours, removing the filter residue by vacuum filtration to obtain a liquid phase containing broad bean extract and water; S3 put the filtrate into a petri dish, seal the open side of the petri dish with plastic wrap and put it in the refrigerator to cool; S4 punches holes in the frozen sample and performs vacuum freeze drying to finally obtain broad bean extract, i.e., corrosion inhibitor.

[0006] Preferably, the drying temperature in S1 is 50-55° C., and the drying time is 36-48 h.

[0007] Preferably, the mass ratio of broad bean powder to deionized water in S2 is 1:25-35.

[0008] Preferably, the refrigeration temperature in S3 is -30°C to -20°C, and the time is 5-12 h.

[0009] Preferably, the freezing temperature in S4 is -130°C to -100°C, and the time is 24-36 hours.

[0010] Based on the same inventive concept, the present invention also provides an application of a broad bean extract corrosion inhibitor (hereinafter referred to as corrosion inhibitor) for preparing an alkaline electrolyte for a zinc-air battery. The specific preparation method is: adding 0.01-0.03 parts of the broad bean extract corrosion inhibitor to 100 parts of a 6M strong alkaline solution and stirring evenly to obtain an alkaline electrolyte for a zinc-air battery.

[0011] Preferably, the strong base is sodium hydroxide.

[0012] The mechanism of action is: in the zinc-air battery reaction, the corrosion inhibitor extracted from broad beans contains a variety of bioactive compounds, polyphenol compounds, flavonoid compounds, etc. These substances are preferentially adsorbed on the surface of the zinc anode and produce a protective film, preventing water molecules from directly contacting the surface of the zinc anode, inhibiting the electrochemical corrosion reaction of the metal, and significantly enhancing the power density and specific capacity.

[0013] The above one or more technical solutions of the present invention have the following technical effects: (1) The present invention uses broad bean extract as a corrosion inhibitor, which broadens the electrochemical stability window of the electrolyte and improves the stability of the electrolyte.

[0014] (2) The present invention uses broad beans as raw materials, which are a renewable resource with a wide source and low cost. The preparation process of broad bean extract is relatively simple and does not involve the use of toxic and harmful substances, which complies with the policy requirements of green emission reduction, energy conservation and environmental protection.

[0015] (3) In the present invention, bioactive substances such as polyphenol compounds and flavonoid compounds in the broad bean extract can be effectively adsorbed on the surface of the zinc anode to form a protective film, which effectively inhibits the corrosion reaction of zinc in alkaline solution, reduces hydrogen evolution and dendrite growth, and improves the Coulomb efficiency and anode utilization rate of the zinc-air battery.

[0016] (4) In the present invention, as the concentration of the broad bean extract corrosion inhibitor increases, the corrosion rate gradually decreases. When the concentration of the broad bean extract is 300 mg / L, the corrosion inhibition efficiency reaches 88.89%.

[0017] (5) The alkaline electrolyte for zinc-air battery prepared by adding broad bean extract corrosion inhibitor can significantly improve the power density and specific capacity of the battery, and the specific capacity can reach 393.7 mA·h·g −1 , extending the battery life while reducing safety risks. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 A process for preparing alkaline electrolyte for zinc-air batteries; Figure 2 The open circuit potential curve of the three-electrode system assembled by Example 6 and the comparative example; Figure 3 1 is a potential polarization curve diagram of Example 6 and a comparative example; Figure 4 The AC impedance diagrams of Example 6 and the comparative example; Figure 5 The electron scanning microscope images of Example 6 and the comparative example; Figure 6 The zinc-air battery assembled from Example 6 and the comparative example was charged at a current of 1 mAcm -2 The constant current discharge curve below. DETAILED DESCRIPTION

[0019] Example 1 A method for preparing a broad bean extract corrosion inhibitor comprises the following steps: S1: Wash the broad beans with deionized water, dry them at 50°C for 36 hours, and grind them into broad bean powder using a grinder; S2: 100 g of broad bean powder was added to 2.5 L of deionized water and boiled for 3-5 hours, and the residue was removed by vacuum filtration to obtain a liquid phase containing broad bean extract and water; S3: Place the filtrate into a culture dish, seal the dish with plastic wrap, and place it in a -30℃ freezer; S4: punch holes in the frozen sample and then freeze-dry it at -100°C in vacuum for 36 hours to finally obtain broad bean extract, i.e., corrosion inhibitor.

[0020] Example 2 A method for preparing a broad bean extract corrosion inhibitor comprises the following steps: S1: Wash the broad beans with deionized water, dry them at 50°C for 48 hours, and grind them into broad bean powder using a grinder; S2: 100 g of broad bean powder was added to 3 L of deionized water and boiled for 3-5 hours, and the residue was removed by vacuum filtration to obtain a liquid phase containing broad bean extract and water; S3: Place the filtrate into a culture dish, seal the open side of the dish with plastic wrap and place it in a -25℃ refrigerator to freeze; S4: punch holes in the frozen sample and then freeze-dry it at -110°C in vacuum for 24 hours to finally obtain broad bean extract, i.e., corrosion inhibitor.

[0021] Example 3 A method for preparing a broad bean extract corrosion inhibitor comprises the following steps: S1: Wash the broad beans with deionized water, dry them at 60°C for 48 hours, and grind them into broad bean powder using a grinder; S2: 100 g of broad bean powder was added to 3.5 L of deionized water and boiled for 3-5 hours, and the residue was removed by vacuum filtration to obtain a liquid phase containing broad bean extract and water; S3: Place the filtrate into a culture dish, seal the open side of the dish with plastic wrap and place it in a -20℃ freezer; S4: punch holes in the frozen sample and then freeze-dry it at -130°C in vacuum for 24 hours to finally obtain broad bean extract, i.e., corrosion inhibitor.

[0022] Example 4 0.01 g of the broad bean extract prepared in Example 3 was added to 100 mL of 6 M NaOH and stirred to obtain an alkaline electrolyte for zinc-air batteries (corrosion inhibitor concentration: 100 mg / L).

[0023] Example 5 0.02 g of the broad bean extract prepared in Example 3 was added to 100 mL of 6 M NaOH and stirred to obtain an alkaline electrolyte for zinc-air batteries (corrosion inhibitor concentration: 200 mg / L).

[0024] Example 6 0.03 g of the broad bean extract prepared in Example 3 was added to 100 mL of 6 M NaOH and stirred to obtain an alkaline electrolyte for zinc-air batteries (corrosion inhibitor concentration: 300 mg / L).

[0025] Comparative Example The difference between this comparative example and Example 6 is that when preparing the electrolyte, no corrosion inhibitor for zinc-air battery is added, 24 g NaOH is weighed, dissolved in deionized water, cooled to room temperature, and fixed to volume in a 100 mL volumetric flask to obtain 100 mL, 6 mol / L sodium hydroxide solution, i.e., the electrolyte (Blank).

[0026] Experimental Section In order to further verify the effect of the electrolyte prepared by the present invention on the self-corrosion performance and discharge performance of the zinc anode, test examples 1-4 were respectively subjected to electrochemical tests, corrosion degree tests of metal zinc electrodes and discharge performance tests. Among them, industrial pure zinc with a purity of 99.99% was used as the zinc negative electrode of the alkaline zinc-air battery. Before the experiment, it was polished with 400, 800, 1500, and 2000 grit sandpaper in sequence, and then ultrasonically washed with anhydrous ethanol and deionized water in sequence, and then dried at room temperature. The specific test examples are as follows:

[0027] Test Example 1 Electrochemical tests were performed on the electrolytes prepared in Examples 4-6 and Comparative Example using a conventional three-electrode system on a CHI760E electrochemical workstation. The working electrode (WE), counter electrode (CE), and reference electrode (RE) were as follows: 2 The zinc sample, platinum electrode and saturated calomel electrode equipped with Luggin capillary were immersed in the electrolyte prepared in Examples 4-6 and Comparative Example to stabilize the corrosion potential, and the open circuit potential (OCP) change was recorded within 1000s. The results are as follows: Figure 2 As shown, from Figure 2 It can be seen that compared with the Blank group, with the increase of time, the open circuit potential curve (OCP curve) containing the added corrosion inhibitor (Example 4-6: corrosion inhibitor concentration 100-300 mg / L) all moved negatively. This is due to the passivation reaction of the anode. Subsequently, with the increase of immersion time, the potential gradually reached a stable state.

[0028] According to the open circuit potential (OCP), at 10 5 ~10 −2 Electrochemical impedance spectroscopy (EIS) was performed in the Hz frequency range with an amplitude of 5 mV. Figure 4 As shown, Figure 4 is the AC impedance diagram of Example 6 and the comparative example; Figure 4 It can be seen that the larger the radius of the semicircle in the AC impedance diagram, the greater the charge transfer resistance between the solution and the zinc interface ( R ct ) is larger, thus the corrosion inhibition efficiency is higher; on the contrary, if the radius is smaller, the transfer charge resistance between the solution and the zinc interface ( R ct ) is smaller, the lower the corrosion inhibition efficiency is. The corrosion inhibition efficiency is calculated by the following formula ( η ):

[0029] in, R inh and R 0 are R with and without corrosion inhibitor.ct After calculation, it can be concluded that the corrosion inhibition efficiencies of 100 mg / L, 200 mg / L and 300 mg / L are 77.27%, 80.00% and 88.89% respectively.

[0030] Then, the potentiodynamic polarization curve (PDP) was tested at a scan rate of 0.001 mVs in the potential range of ±250 mV relative to the open circuit potential (OCP). Figure 3 As shown, from Figure 3 The potentiodynamic polarization curves of broad beans in 6 mol / L sodium hydroxide solution (blank sample) and at different concentrations are used. The corrosion inhibition efficiency is calculated by the following formula using the corrosion current density ( η i )as follows:

[0031] in, i corr(0) and i corr(inh) are the current density of the blank sample and the current density with added corrosion inhibitor. After calculation, it can be concluded that the corrosion inhibition efficiencies of 100 mg / L, 200 mg / L and 300 mg / L are 75.21%, 78.33% and 86.67% respectively. The anode of all broad bean extract concentration polarization curves moves to the area with lower current density, which indicates that broad bean extract is an anodic corrosion inhibitor that can inhibit the corrosion of anode metal zinc.

[0032] Test Example 2 After the metal zinc electrode was immersed in the electrolyte prepared in Example 6 and the comparative example for 12 hours, an electron scanning microscope was used to observe the surface morphology of the zinc anode, and an electron scanning microscope analysis was performed to observe the surface changes of the metal zinc. The results are as follows: Figure 5 As shown, Figure 5 In the figure, from left to right are respectively an optical microscope image of a metal zinc electrode, an optical microscope image of a metal zinc electrode immersed in a comparative example for 12 hours, and an optical microscope image of a metal zinc electrode immersed in Example 6 for 12 hours; it can be seen from the figure that in the comparative example, with the addition of broad bean extract, the pitting corrosion on the surface of the zinc anode is reduced, and in the electrolyte of broad bean extract, its corrosion rate is low.

[0033] Test Example 3 In order to explore the specific effect of electrolyte on the discharge performance of zinc-air batteries, we conducted the following experiments: First, 150 ml of each electrolyte prepared in Example 6 and the comparative example was placed in a plastic washing bottle. Then, each of the above electrolytes was circulated through a connected full-battery device, and a circulation pump was equipped outside the device to drive the circulation flow of the electrolyte at a rate of 7 ml / min. Then, we charged the electrolyte at 1 mAcm - ²) under the condition of constant current, the zinc-air battery was discharged and its discharge curve was recorded. The experimental results are as follows Figure 6 As shown in the figure, the constant current discharge performance of zinc-air batteries under different electrolytes is shown in the figure. Figure 6 It can be seen that the specific capacity of Example 6 reaches 393.7 mAh / g, and the specific capacity of the comparative example is 282.5 mAh / g. The specific capacity of Example 6 is significantly improved compared with the comparative example.

Claims

1. A method for preparing a broad bean extract corrosion inhibitor, characterized in that: The steps include: S1, clean the broad beans with deionized water, and grind them into broad bean powder using a grinder after drying; S2, adding broad bean powder to deionized water and boiling for 3-5 hours, removing the filter residue by vacuum filtration to obtain a filtrate containing broad bean extract and water; S3. Put the filtrate into a culture dish, seal the open surface of the culture dish with plastic wrap and put it into the refrigerator to freeze; S4. Roll the frozen sample and perform vacuum freeze drying to finally obtain broad bean extract, i.e., corrosion inhibitor.

2. The method for preparing the broad bean extract corrosion inhibitor according to claim 1, characterized in that: In S1, the drying temperature is 50-55° C. and the drying time is 36-48 h.

3. The method for preparing the broad bean extract corrosion inhibitor according to claim 1, characterized in that: The particle size of the broad bean powder in S1 is 0.148 mm.

4. The method for preparing a corrosion inhibitor for zinc-air batteries according to claim 1, wherein: The mass ratio of broad bean powder to deionized water in S2 is 1:25-35.

5. The method for preparing the broad bean extract corrosion inhibitor according to claim 1, characterized in that: The refrigeration temperature in S3 is -30°C to -20°C, and the refrigeration time is 5 to 12 hours.

6. The method for preparing the broad bean extract corrosion inhibitor according to claim 1, characterized in that: The freezing temperature in S4 is -130°C to -100°C, and the freezing time is 24-36 hours.

7. The use of the broad bean extract corrosion inhibitor prepared by the method according to any one of claims 1 to 6, characterized in that: The invention is used for preparing an alkaline electrolyte for zinc-air batteries. The specific preparation method is as follows: 0.01-0.03 parts of a corrosion inhibitor are added into 100 parts of a 6M strong alkaline solution and stirred evenly to obtain an alkaline electrolyte for zinc-air batteries.

8. The use of the broad bean extract corrosion inhibitor according to claim 7, characterized in that: The strong base is sodium hydroxide.

9. The use of the broad bean extract corrosion inhibitor according to claim 8, characterized in that: The concentration of the corrosion inhibitor is 100 mg / L-300 mg / L.

10. The use of the broad bean extract corrosion inhibitor according to claim 9, characterized in that: The concentration of the corrosion inhibitor is 300 mg / L.